Characterization of micro-RNA Profile in the Blood of Patients with Marfan's Syndrome - Abu-Halima, Masood; Ludwig, Nicole; Rädle-Hurst, Tanja; Keller, Andreas; Motsch, Lars; Marsollek, Ina; El Rahman, Mohammed Abd; Abdul-Khaliq, Hashim; Meese, Eckart (The Thoracic and Cardiovascular Surgeon, 2018)
Background Marfan's syndrome (MFS) is an autosomal dominant inheritance disorder with a 1/5,000 live-birth prevalence. It is characterized by a wide range of clinical manifestations with more than 3,000 mutations identified in the FBN1 gene. In this study, we aimed to determine if specific patterns of circulating micro-RNAs (miRNAs) are associated with MFS-associated with cardiovascular diseases.Methods Microarray-based miRNA profiling was performed on blood samples of 12 MFS patients, and 12 healthy volunteers (HVs) controls and the differences in miRNA abundance between the two groups were validated using independent cohorts of 22 MFS and of 22 HV controls by real-time quantitative polymerase chain reaction (RT-qPCR). Enrichment analyses of altered miRNA abundance were predicted using bioinformatics tools.Results Altered miRNA abundance levels were determined between MFS (n = 34) and HVs (n = 34). In a screening phase, we analyzed 12 patients with MFS and 12 HVs by miRNA microarray. We found 198 miRNAs that were significantly altered in MFS patients as compared with HVs, including 16 miRNAs with a more than 1.5-fold change. Out of these 16 miRNAs, 10 showed a decreased abundance and 6 showed an increased abundance. In the validation phase, we analyzed independent cohorts of 22 MFS and of 22 HV controls by RT-qPCR. We confirmed the direction of abundance changes and the significance of different abundances between MFS patients and HVs for four miRNAs, namely, miR-362–5p, miR-339–3p, miR-340–5p, and miR-210–3p. Only the miR-150–5p showed a significant correlation with mitral valve prolapse (p = 0.010). The predicted targets for the validated miRNAs were associated with signal transduction, tissue remodeling, and cellular interaction pathways.Conclusion The altered abundance level of different miRNAs in whole blood of MFS patients lays the ground to the development of novel diagnostic approaches with altered miRNAs levels associated with MFS with manifestations associated with cardiovascular diseases.
Keywords: Micro-RNA; Marfan syndrome; fibrillin